2003
DOI: 10.1103/physrevb.68.224504
|View full text |Cite
|
Sign up to set email alerts
|

Directional vortex motion guided by artificially induced mesoscopic potentials

Abstract: Rectangular pinning arrays of Ni dots define a potential landscape for vortex motion in Nb films. Magnetotransport experiments in which two in-plane orthogonal electrical currents are injected simultaneously allow one to select the direction and magnitude of the Lorentz force on the vortex lattice, thus providing the angular dependence of the vortex motion. The background dissipation depends on the angle at low magnetic fields, which is progressively smeared out with increasing field. The periodic potential lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
55
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 19 publications
1
55
2
Order By: Relevance
“…This type of channeling has been seen elsewhere. [17][18][19] We emphasize that the ratchet reversal is well established experimentally in superconducting films with arrays of structurally asymmetric pinning sites, but its origin is very controversial. There are different models used to explain the 174507-3 presence of this reversal.…”
Section: Discussionmentioning
confidence: 94%
“…This type of channeling has been seen elsewhere. [17][18][19] We emphasize that the ratchet reversal is well established experimentally in superconducting films with arrays of structurally asymmetric pinning sites, but its origin is very controversial. There are different models used to explain the 174507-3 presence of this reversal.…”
Section: Discussionmentioning
confidence: 94%
“…In addition to the colloidal work, symmetry locking effects have been further studied for superconducting vortices in numerical simulations [22,23] and have also been observed experimentally [22,24,25,26]. For systems in which the particles are strongly interacting, dynamical symmetry locking effects can occur even when the particles are moving over a random substrate provided that the particle-particle interactions are strong enough to overcome the randomness of the substrate and produce a triangular ordering of the moving particles [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Recent progress in the fabrication of nanostructures provided the possibility to realize superconducting thin films which contain artificial defects as pinning sites with well-defined size, geometry and spatial arrangement. In particular, artificially produced periodic arrays of submicron holes (antidots) [5,6,7,8] and magnetic dots [9,10,11,12] as pinning sites have been intensively investigated during the last years, to address the fundamental question how vortex pinning -and thus the critical current density j c in superconductors -can be drastically increased.In this context, it has been shown that a very stable vortex configuration, and hence an enhancement of the critical current I c occurs when the vortex lattice is commensurate with the underlying periodic pinning array. This situation occurs in particular at the so-called first matching field B 1 = Φ 0 /A, i.e., when the applied field B corresponds to one flux quantum Φ 0 = h/2e per unit-cell area A of the pinning array.…”
mentioning
confidence: 99%